Inhibitory Effect and Mechanism of Procyanidin B2 on High Glucose-Induced Ferroptosis in SH-SY5Y Cells - WANG Jiaqi, CHEN Xiuting, XIA Xing, ZHOU Jinling (Shipin Kexue)
Objective: To investigate the neuroprotective effect and mechanism of procyanidin B2 on high glucose-induced ferroptosis in differentiated SH-SY5Y cells. Methods: An in vitro cell injury model was created by treating differentiated SH-SY5Y cells with 45 mmol/L glucose, and the cells were randomly divided into normal control, high-glucose model, high-concentration procyanidin B2 treatment, low-concentration procyanidin B2 treatment, and positive control drug lipvastatin-1 groups. The CCK8 method was used to observe cell viability. Flow cytometry was used to detect Fe2+ and lipid peroxide (LPO) levels, immunofluorescence was used to detect lipid reactive oxygen species (ROS) levels, JC-1 staining was used to detect mitochondrial membrane potential, transmission electron microscopy (TEM) was used to observe morphological changes characteristic of mitochondrial ferroptosis, and Western blot was used to detect the expression levels of ferroptosis-related proteins including solute carrier family 7 member 11 (SLC7A11) and transferrin receptor (TFRC). Results: Compared with the normal control group, the high glucose model group showed a significant decrease in cell viability and mitochondrial membrane potential, reduced glutathione (GSH)/oxidized glutathione (GSSG) ratio, and SLC7A11 protein expression level, while the intracellular levels of Fe2+, LPO, lipid ROS, and TFRC increased obviously. Compared with the high glucose group, a certain concentration of procyanidin B2 significantly increased cell viability, mitochondrial membrane potential, GSH/GSSG ratio, and SLC7A11 protein expression and simultaneously down-regulated LPO and lipid ROS levels. The TEM results showed that procyanidin B2 significantly alleviated mitochondrial shrinkage, cristae rupture and disappearance, and other distortions caused by high glucose. Conclusion: Procyanidin B2 can inhibit lipid peroxidation damage induced by high glucose in differentiated SH-SY5Y cells, and its action mechanism is related to the inhibition of ferroptosis by regulating the glutathione pathway.